ANOMIE IN AMERICAN BUSINESS SYSTEM AS AN AFTERMATH OF THE AMERICAN DREAM: DAVID MAMET’S “AMERICAN BUFFALO” AND “GLENGARRY GLEN ROSS” - Kocsoy, F. Gul; Güzelçiçek, Eda (My University, 2021)
In this article, the concept of ‘anomie’ in David Mamet’s (1947-) “American Buffalo” (1976) and “Glengarry Glen Ross” (1984) is analysed in the context of the economic and socio-cultural evolution of America and ‘The American Dream of Success’. It is shown how virtues and values with the mentality of the system and with the name of ‘business’ transform into exploitable commodifications in the plays, which are designed as the microcosms of American capitalist business system. The anomic characters who behave under the pressures of the material success based American dream and with the malpractices of the American business system transgress the ethic conceptions and norms in the course of their struggle of survival; they keep pace with this order, legalize and normalize it. Moreover, they commit crimes for the sake of material gain and in the name of business, individually and collectively. The unbalance between the characters’ right and ordinary aim of existence/being successful and the unethical means they employ to reach it forms the state of anomie and gives way to their inclination to behavioral deviation and violence. In the study, the negative results of the lack of ethics on individuals and society are presented referring to the anomie theories of Emile Durkheim, Robert Merton, Steven F. Messner and Richard Rosenfeld. The disruptive influences of American business system’s norms, which disregard ethics and the individual and social conflicts they generate are exhibited.
Keywords: Anomie; American Dream; David Mamet; “American Buffalo” “Glengarry Glen Ross”.